PRESIDENTIAL ADDRESS: Lessons from Africa: Ubuntu, solidarity, dignity, kinship, and humility - Jecker, Nancy (Bioethics, 2024)
This paper addresses bioethics in the context of the coronavirus disease 2019 (COVID-19) pandemic. The Introduction (Section 1) highlights that at the field's inception, infectiousness was not front and center. Instead, infectious disease was widely perceived as having been conquered. This made it possible for bioethicists to center values such as individual autonomy, informed consent, and a statist conception of justice. Section 2 urges shifting to values more fitting for the moment the world is in. To find these, it directs attention to the Global South, and in particular, Africa, and to the values of ubuntu, solidarity, dignity, kinship, and humility. The paper concludes (in Section 3) that 21st-century challenges facing bioethics are increasingly global, and calls on bioethicists themselves to be more globally inclusive in their approaches.